2009
DOI: 10.1186/1476-5918-8-6
|View full text |Cite
|
Sign up to set email alerts
|

The effects of age on skeletal muscle and the phosphocreatine energy system: can creatine supplementation help older adults

Abstract: Creatine supplementation has been found to significantly increase muscle strength and hypertrophy in young adults (≤ 35 yr) particularly when consumed in conjunction with a resistance training regime. Literature examining the efficacy of creatine supplementation in older adults (55-82 yr) suggests creatine to promote muscle strength and hypertrophy to a greater extent than resistance training alone. The following is a review of literature reporting on the effects of creatine supplementation on intramuscular hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 70 publications
(123 reference statements)
0
28
0
4
Order By: Relevance
“…It is recommended to have an adequate creatine supplementation because it could represent an intriguing intervention to counteract sarcopenia and in particular fatigue associated with sarcopenia; the timing of creatine ingestion (i.e., 0.03-0.5 g/kg before and after the sessions of resistance training) can be more relevant than the amount of creatine [73,76] The ingestion of an adequate creatine supplementation determines the increase in muscle phosphocreatine (PCr) and the energy provided for the phosphorylation of adenosine diphosphate (ADP) to adenosine triphosphate (ATP) during and after intense exercise largely depends on the amount of PCr stored in the muscle Vitamin D…”
Section: Creatinementioning
confidence: 99%
See 1 more Smart Citation
“…It is recommended to have an adequate creatine supplementation because it could represent an intriguing intervention to counteract sarcopenia and in particular fatigue associated with sarcopenia; the timing of creatine ingestion (i.e., 0.03-0.5 g/kg before and after the sessions of resistance training) can be more relevant than the amount of creatine [73,76] The ingestion of an adequate creatine supplementation determines the increase in muscle phosphocreatine (PCr) and the energy provided for the phosphorylation of adenosine diphosphate (ADP) to adenosine triphosphate (ATP) during and after intense exercise largely depends on the amount of PCr stored in the muscle Vitamin D…”
Section: Creatinementioning
confidence: 99%
“…Chilibeck et al (2005) showed a greater increase (3.2 versus 1%) of bone mineral content in older men (71 years) after 12 weeks of creatine supplementation (0.3 g/kg for 5 days, 0.07 g/kg for 11 weeks), in combination with training against resistance compared to training alone [75]. Dalbo et al (2009) have stated that creatine is an effective intervention to combat sarcopenia [76]. The timing of creatine ingestion (i.e., 0.03-0.5 g/kg before and after the sessions of resistance training) can be more relevant than the amount of creatine.…”
Section: 2mentioning
confidence: 99%
“…Aging also leads to a decline in total creatine and phosphocreatine (PCr) in muscles (21,22). Furthermore, the rate of post exercise PCr synthesis decreases about 8% in every decade of life after the age of 30 (22). Existing evidences suggest that creatine supplementation may reverse these events and could subsequently improve performance in daily activities (20).…”
Section: Introductionmentioning
confidence: 99%
“…By reviewing the existing evidences, Dalbo et al (2009) concluded that creatine supplementation is an effective nutritional intervention for diminishing Sarcopenia in the elderly, especially, if it is combined with resistance-type exercises (22).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation